Perceptions of the High School Councellor in Alberta - Mott, T. R. (Canadian Journal of Counselling and Psychotherapy, 2012)
It was the purpose of this study to investigate perceptions of the role of the high school counsellor between groups and among members of each group of school counsellors, teachers, and principals in Alberta high schools. Ninety-two high schools in Alberta were selected to participate in the investigation. The high school principal, a school coun- sellor, and a selected high school teacher from each of the participating schools were asked to complete an identical questionnaire. Respondents were asked to study each item on the questionnaire and record the degree of acceptance, implementation, and importance of each described activity. Results revealed that counsellor, teacher, and principal groups agreed on the role functions of the secondary school counsellor; however, significant differences were found between the teacher group and coun- sellor group and between the teacher group and principal group on the implementation dimension. Sigmificant differences were also found between the counsellor and teacher groups and between the counsellor and principal groups on the importance dimension. There were no significant relationships found between rural and urban counsellor, teacher, or principal groups on any of the three dimensions under investigation.